Eksistensi Peranan Jaksa Dalam Pelaksanaan Pembayaran Uang Pengganti - Arie Satria Hadi Pratama (Corruptio, 2020)
Alternative provisions as regulated in Article 18 (2) and (3) of the Corruption Eradication Act pose a problem for the Prosecutor in executing court decisions thet impose additional crimes in the form of payment of replacement money to the convicted person. The problem in this study is how the role of the prosecutor in the implementation of payment of money in liue of corruption and why there are inhibiting factors in the implementation of payment of money in lieu of corruption.